Global Culture Reproduction Through The String Orchestra’ Repertoire - Ferry Matias (JOMANTARA, 2021)
The selection of repertoire on a musical ensemble is quite important, especially in the context of rehearsal in the non-professional string ensemble community. It is very common if there is a diversity of skill levels in each member. Such diversity will usually be a common obstacle when it comes to determining a shared repertoire. An overly difficult repertoire (advance) will be difficult for some members otherwise an easy one will create a bored atmosphere for members who are already proficient. Even the role of unbalanced work will make some members may struggle while others will become bored so that the rehearsal atmosphere is not conducive. The author observed that there is an interesting repertoire that is often used as an ensemble rehearsal material in the bowed string’s formation, namely Brandenburg Concerto no. III BWV 1048 Part III in G Major by Johan Sebastian Bach for 3 violins, 3 violas, 3 cellos and 1 double bass. This work is often used as an alternative work together in the community environment of string orchestras in Bandung, and based on the observation of the author of this work is often used in several workshops and ensemble learning materials, with a relatively balanced role, this complex-sounding work has techniques and finger positions that can still be reached by players in the skill range level 3-5 ABRSM. The authors collected data through observations, interviews and documentation on Unpas Music Study Program students who had played this work. After being described and analyzed, the authors found that this work had a significant role in improving ensemble skills playing in string ensembles that would indirectly also improve their individual skills especially for advanced entry-level string instrument students.